USE OF INFORMATION AND COMMUNICATION TECHNOLOGY IN TEACHING PHYSICS - Alloqulov Mirzabek; Bultakova Sarvara; Hasanova Hafiza (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Information and Communication Technology (ICT) is beginning to be recognized as one of the major instructional components, especially in science subjects. The article looked at the importance of teacher’s knowledge and learner’s interactions in Physics learning; applications of ICT in Physics education; benefits of ICT in teaching and learning Physics in secondary schools.